2021
DOI: 10.3390/pathogens10121599
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Viral Membrane Fusion by Peptides and Approaches to Peptide Design

Abstract: Fusion of lipid-enveloped viruses with the cellular plasma membrane or the endosome membrane is mediated by viral envelope proteins that undergo large conformational changes following binding to receptors. The HIV-1 fusion protein gp41 undergoes a transition into a “six-helix bundle” after binding of the surface protein gp120 to the CD4 receptor and a co-receptor. Synthetic peptides that mimic part of this structure interfere with the formation of the helix structure and inhibit membrane fusion. This approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 188 publications
(227 reference statements)
0
12
0
Order By: Relevance
“…Costin et al ( 2010 ) designed a peptide AVP1056 (DN57opt), which interacts with the Dengue Virus E protein and inhibits viral infection in culture. The peptide AVP1056 inhibits virus binding to cells through binding directly to the E protein (Düzgüneş et al 2021 ). In our molecular docking study, AVP1056 is ranked first (docking score of -305.87) and interacts with ARG107, PHE104, SER108, TYR63, SER60, and SER110 residues of the modeled RBD of omicron (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Costin et al ( 2010 ) designed a peptide AVP1056 (DN57opt), which interacts with the Dengue Virus E protein and inhibits viral infection in culture. The peptide AVP1056 inhibits virus binding to cells through binding directly to the E protein (Düzgüneş et al 2021 ). In our molecular docking study, AVP1056 is ranked first (docking score of -305.87) and interacts with ARG107, PHE104, SER108, TYR63, SER60, and SER110 residues of the modeled RBD of omicron (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibitors able to prevent this structural refolding offer a great deal of therapeutic and commercial potential since they block the infection prior to the virus’ entry into the host cells. FP inhibitors have not been largely used for interfering with the fusion/entry process with respect to HR-derived inhibitors [ 44 , 54 , 55 , 56 , 57 , 58 ]. To date, only a few studies have reported FP-targeted peptides as anti-HIV agents [ 59 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Viral S protein interacts with receptor and then virus particles are wrapped in endosomes to enter host cells [ 72 ]. In endosomes, the viral envelope and membrane structure of endosomes are fused in the environment of cathepsin L (CTSL) and low pH to release the viral genome into the host cytoplasm [ 73 ]. The other is membrane fusion, through which exogenous proteases or host proteases activate the S protein upon the binding of the virus to the receptor, and that virus then enters the cytoplasm through membrane fusion.…”
Section: Secov Infection and The Involvement Of Host Factorsmentioning
confidence: 99%